2013
DOI: 10.1073/pnas.1218510110
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of mouse subplate reveals a dynamic gene network and disease association with autism and schizophrenia

Abstract: The subplate zone is a highly dynamic transient sector of the developing cerebral cortex that contains some of the earliest generated neurons and the first functional synapses of the cerebral cortex. Subplate cells have important functions in early establishment and maturation of thalamocortical connections, as well as in the development of inhibitory cortical circuits in sensory areas. So far no role has been identified for cells in the subplate in the mature brain and disease association of the subplate-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
139
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 62 publications
11
139
1
Order By: Relevance
“…This is consistent with recent data showing that preterm infants have higher rates of neuropsychiatric disease in adult life, 68 as well as the observation that schizophrenia-and autism-associated genes are overexpressed in developing mouse cortical subplate, 69 a region of specific vulnerability during preterm life. 70 Future research could focus on perturbations in neuronal migration and lipid metabolism in the causal pathway to preterm brain injury.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with recent data showing that preterm infants have higher rates of neuropsychiatric disease in adult life, 68 as well as the observation that schizophrenia-and autism-associated genes are overexpressed in developing mouse cortical subplate, 69 a region of specific vulnerability during preterm life. 70 Future research could focus on perturbations in neuronal migration and lipid metabolism in the causal pathway to preterm brain injury.…”
Section: Discussionsupporting
confidence: 92%
“…Subplate cells are some of the earliest generated neurons in cortex (Rakic and Kostovic, 1990; Hoerder‐Suabedissen et al, 2009; Oeschger et al, 2012; Hoerder‐Suabedissen, 2013). These studies strengthen the hypothesis that an embryonic subplate was present in the ancestors of mammals and that additional cellular populations evolved as cortical development and connectivity became more complex (Montiel et al, 2011; Wang et al, 2011a).…”
Section: Exploring Brain Evolution From Transcriptome Databasesmentioning
confidence: 99%
“…At both E18 and P8, some RMTW-derived cells expressed complexin 3 (Cplx3; Figs. S1F and S2A), a synaptic protein and marker of early-born subplate neurons in the mouse (17).…”
Section: Significancementioning
confidence: 99%
“…The subplate is a heterogeneous cell population (6,17,32,33), with the wide variety of cell types suggesting multiple origins (34). Indeed, we have shown that different subplate cell populations are generated in both cortical and extracortical areas.…”
Section: Subplate Phenotypic Heterogeneity Correlates With Ontogenicmentioning
confidence: 99%